Targeting the type 1 insulin-like growth factor receptor as a treatment for cancer. - Yuen, J; Macaulay, V (2008)
BACKGROUND: The type 1 insulin-like growth factor receptor (IGF1R) plays a critical role in transformation, invasion and apoptosis protection, and is an attractive cancer treatment target. OBJECTIVE: To review IGF1R antibodies and kinase inhibitors that are in preclinical and clinical development, and to discuss questions that will influence the success of this approach in clinical practice. METHODS: This review is drawn from published literature, meeting abstracts and online resources. RESULTS/CONCLUSION: IGF1R blockade is generally well tolerated although it can induce hyperglycaemia. Single-agent activity has been documented in Ewing's sarcoma but not thus far in common solid tumours. Key issues include identification of factors that influence sensitivity to IGF1R blockade, and how most effectively to combine IGF1R inhibitors with other treatments.